Uranium halide complexes stabilized by a new sterically demanding tripodal tris(N-adamantylamidodimethylsilyl)methane ligand. Issue 11 (2nd July 2016) - King, David M.; Gardner, Benedict M.; Lewis, William; Liddle, Stephen T.
Abstract: The new tris ( N -adamantylamine-dimethylsilyl)methane HCSiMe2 N(H)Ad3 (Ts Ad H3, 1 ) and its trilithium salt [HCSiMe2 N(Li)Ad3 ] (Ts Ad Li3, 2 ) were synthesized and characterized by multinuclear NMR and IR spectroscopy, elemental microanalysis, and single-crystal X-ray diffraction (XRD). The utility of2 as a ligand transfer reagent for uranium was examined by targeting Ts Ad -uranium(IV) and (III) complexes via its reaction with UCl4 and UI3 (THF)4 ; however, the crystalline material isolated, [U(Ts Ad )(Cl)(μ-Cl)Li(THF)3 ] (4 ) and [U(Ts Ad )U(I)] (5 ), are products of lithium chloride inclusion and uranium disproportionation/ligand redistribution, respectively, and hints at the wide scope of reactivity accessible to Ts Ad -uranium complexes. Complex5 was also independently synthesized stepwise in good yield from2 via treatment with UCl4 and, subsequently, Me3 SiI. The uranium complexes were characterized by a combination of NMR and IR spectroscopy, elemental microanalysis, magnetometric methods, and single-crystal XRD. Abstract :